Comparison of the growth performance of available layer strains in Bangladesh - Emran, AKM; Dey, B; Das, SC; Ray , BC; Rahaman , Z (Bangladesh Journal of Animal Science, 2022)
Various factors have been reported that affect the growth performance of layers, such as genetics, nutrition, environment, and disease. Attaining appropriate growth is essential to ensure profit. The present study was conducted to make comparative analyses of the growth performance of four commonly available layer strains in Bangladesh. A total number of 400-layer day-old chicks (DOCs), 100 from each of NOVOgen brown, ISA brown, Hy-Line brown and Bovans brown were used for the experiment. The birds were equally divided and randomly assigned to 4 treatments having 4 replications in each treatment comprising 25 birds per replication. All birds fed diet with similar composition and provided with the identical care and management up to 16 weeks of age. The results from this study revealed that there were no significant differences among the growth performances (weekly body weight, feed intake, uniformity and survivability) of four commonly available layer strains and all the strains followed the standard very closely. There were also no statistical differences based on the economic parameters of the strains compared in this study. Taken together, it may be concluded that the layer strains available in Bangladesh are highly competitive and suitable for local climatic conditions and the farmers can rely any of them. Bangladesh Journal of Animal Science 51 (4): 163-168